Local Government in Migrant Worker Governance (Case Study in Kabupaten Indramayu, West Java, Indonesia) - Indriyati Caturiani, Susana (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Kabupaten (district) Indramayu is the second largest district as the sender of an overseas worker following Kabupaten Lombok Timur, West Nusa Tenggara. The big part of them is woman, working as domestic helper, babysitter and caregiver. The government of Indonesia stop sending overseas workers for individual users to the countries of the Middle East region gradually. Today, they are turning work to East Asia (Taiwan and Hong Kong), Southeast Asia (Singapore, Malaysia, Brunei Darussalam). Meanwhile, a small portion of migrant workers are men. Usually, they work in Taiwan as the crew of the fishing, fishponds or manufacture , others work as factory workers in South Korea. Migrant worker governance consist of three stages; pre-deployment, deployment and post-deployment . In first stage, the process engages government institution from local, including village, to central. The role of local government is very important for the migrant workers come from there. Dinas Sosial dan Tenaga Kerja (Social and Labor Office) is the government institution that takes care of this problem, however they cannot address themselves because of the complexity of the issue. Two agencies are an important partner for Social and Labor Office is the Village Community Empowerment Office (BPMD) and Women Empowerment and Family Planning Office (BPPKB). The problems that occur, among others document fraud, unprincipled broker and persistence of illegal migrant workers. Coordination between government institution is very crucial, not only at local level but also at central. Nevertheles, this paper will adduce it at local level in pre-deployment stage. This research is qualitative, collecting data through deep interview to informans and observation. Some of the documents used as complementary data. This study find that fraud committed by brokers, known by candidates of overseas worker or their family. Despite the apparent deception led to the crime of human trafficking also occurs. Publishing rules and enforcement procedures that have been performed by several villages have been good, but not enough. Fundamental change is needed is awareness of the villagers generally about safe migration. Meanwhile, the government's inter-agency coordination is still incidental, limited and the lack of leadership capability.